Mapping of intracellular pH in the in vivo rodent heart using hyperpolarized [1-13C]pyruvate - Lau, A; Miller, J; Tyler, D (Wiley, 2016)
Purpose: To demonstrate the feasibility of mapping intracellular pH within the in vivo rodent heart. Introduction: Alterations in cardiac acid-base balance can lead to acute contractile depression and alterations in Ca2+ signalling. The transient reduction in ATP consumption and cardiac contractility may be initially beneficial; however, sustained pH changes can be maladaptive, leading to myocardial damage and electrical arrhythmias. Methods: Spectrally-selective RF pulses were used to excite the HCO3- and CO2 resonances individually while preserving signal from the injected hyperpolarized [1-13C]pyruvate. The large flip angle pulses were placed within a 3D imaging acquisition which exploited CA-mediated label exchange between HCO3- and CO2. Images at 4.5x4.5x5 mm3 resolution were obtained in the in vivo rodent heart. The technique was evaluated in healthy rodents scanned at baseline and during high cardiac workload induced by dobutamine infusion. Results: The intracellular pH was measured to be 7.15±0.04 at baseline, and decreased to 6.90±0.06 following 15 minutes of continuous β-adrenergic stimulation. Conclusion: Volumetric maps of intracellular pH can be obtained following an injection of hyperpolarized [1-13C]pyruvate. The new method is anticipated to enable assessment of stress-inducible ischaemia and potential ventricular arrythmogenic substrates within the ischaemic heart.